The Human and the World in Axiological Space of Contemporary Young Poles (based on questionnaire survey materials) - Żywicka, Beata (Vilnius University Open Series, 2021)
The aim of this study is to outline the image of human and the world shaped in the common linguistic and axiological awareness by contemporary young Poles over the course of 20 years (from 1990 to 2010). The research material comes from experimental data (abbreviated as ASA) collected in three research actions carried out in 1990, 2000 and 2010. In the image of a human, drawn by young respondents, dominated mainly psychosocial (helping others, love, kindness, responsibility, empathy, respect for another human being, understanding, friendship), psychological (intelligence / reasoning, thinking ability, feelings, joy, honesty) and ethical (honesty, morality, dignity, free will, good, honor, living in harmony with one̛s conscience, with values). They created an idealized image of a rational, intelligent man, endowed with human dignity, honest, guided by moral principles, living in harmony with his own conscience. It is a man (homo / persona socialis) who helps other people, coexists, interacts, and cooperates with others because he depends on the social group, and the social group depends on him, which in turn translates into his basic relationships and gained experiences. On the other hand, in the picture of the world cited by ASA respondents, two different ways of understanding it met: purely physical, as a globe, and social, as a community of people. These two perspectives have several common elements. The world identified with the Earth (globe) is perceived as the living environment, the place where people live. It is a human world (res humanae), intended for people because they give it the meaning of existence. The world seen as a diversity that forms a whole, consisting of many life forms coexisting with each other, appears as a specific universe. The analysis of the collected material proved that for contemporary young Poles, the essence of each person is definitely expressed in his humanity, often called human dignity, while the essence of the world is undoubtedly determined by the people who live in it.